Transformation rule:
[tex](x,y)\rightarrow(x-1,y+3)[/tex]Given triangle XYZ
To get X'Y'Z' coordinates of vertices, subtract 1 to the x coordinate and add 3 to the y-coordinate:
[tex]\begin{gathered} X(-2,1)\rightarrow X^{\prime}(-2-1,1+3) \\ X^{\prime}(-3,4) \end{gathered}[/tex][tex]\begin{gathered} Y(-4,-3)\rightarrow Y^{\prime}(-4-1,-3+3) \\ Y^{\prime}(-5,0) \end{gathered}[/tex][tex]\begin{gathered} Z(0,-2)\rightarrow Z^{\prime}(0-1,-2+3) \\ Z^{\prime}(-1,1) \end{gathered}[/tex]Then, the coordinates of vertices in triangle X'Y'Z' are: X'(-3,4), Y'(-5,0) and Z'(-1,1)